The Effect of Personal Branding Instagram Account @tantrinamirah on the Confidence Level of Followers - Tya Jussiva; Yeni Rosilawati (Jogjakarta Communication Conference (JCC), 2023)
The popularity of Instagram gave birth to influencers who use Instagram to build an image for their followers. This study aims to determine how much influence the personal branding built by influencer namely Tantri Namirah on her Instagram towards on the level of confidence of her followers. The sampling technique used convenience sampling, 100 samples were obtained using a questionnaire that had been tested for validity and reliability. The data analysis technique uses simple linear regression. The results of this study are that there is an influence between Tantri Namirah's personal branding on followers' self-confidence with a determination coefficient value of 0.310. The partial t value of this study is 6.927, so the result of this study showed that Tantri Namirah's personal branding on her Instagram had a significantly positive effect on increasing followers' self-confidence.